2007
DOI: 10.1016/j.cell.2007.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine VEGF Signaling Is Required for Vascular Homeostasis

Abstract: Vascular endothelial growth factor (VEGF) is essential for developmental and pathological angiogenesis. Here we show that in the absence of any pathological insult, autocrine VEGF is required for the homeostasis of blood vessels in the adult. Genetic deletion of vegf specifically in the endothelial lineage leads to progressive endothelial degeneration and sudden death in 55% of mutant mice by 25 weeks of age. The phenotype is manifested without detectable changes in the total levels of VEGF mRNA or protein, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
750
3
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 934 publications
(804 citation statements)
references
References 56 publications
41
750
3
10
Order By: Relevance
“…3G) in the engineered MiaPaca2 cells. This result not only demonstrates that VEGF-A mediated signaling dramatically improves VV gene expression and replication but also confirms the previously reported autocrine nature of VEGF-A-mediated signaling (22).…”
Section: Resultssupporting
confidence: 90%
“…3G) in the engineered MiaPaca2 cells. This result not only demonstrates that VEGF-A mediated signaling dramatically improves VV gene expression and replication but also confirms the previously reported autocrine nature of VEGF-A-mediated signaling (22).…”
Section: Resultssupporting
confidence: 90%
“…In addition, deletion of HIF-1a specifically in endothelial cells can also disrupt the VEGF autocrine loop, implicated in angiogenesis of solid tumors (Tang et al, 2004). Furthermore, a recent study using specific deletion of VEGF in endothelial cells has demonstrated that endothelial integrity and survival depends on the maintenance of low-level autocrine VEGF signaling, which is pivotal for maintaining vascular homeostasis (Lee et al, 2007). Therefore, it can be postulated that the crucial function of autocrine VEGF signaling in vascular homeostasis is mediated by the Raf/MEK/ ERK signaling cascade and negatively regulated by endogenous RKTG in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine loops have been previously described in both endothelial and hematopoietic stem cells 25,26 ; however, in both of these systems, treatment with VEGFR antagonists that act extracellularly fail to reverse the effects of VEGF, whereas those that are able to penetrate the intracellular compartment mimic the deletion of VEGF. 25,26 In addition, exogenous treatment with VEGF is unable to compensate for the loss of endogenous VEGF in endothelial cells in which VEGF has been specifically deleted, suggesting the presence of an internal VEGF-dependent autocrine loop. 25 In contrast, we found that treatment with either soluble VEGFR or VEGFR2 neutralizing antibodies can reverse the podocyte proliferation and de-differentiation induced by HIV infection.…”
Section: Brief Communication Wwwjasnorgmentioning
confidence: 99%
“…25,26 In addition, exogenous treatment with VEGF is unable to compensate for the loss of endogenous VEGF in endothelial cells in which VEGF has been specifically deleted, suggesting the presence of an internal VEGF-dependent autocrine loop. 25 In contrast, we found that treatment with either soluble VEGFR or VEGFR2 neutralizing antibodies can reverse the podocyte proliferation and de-differentiation induced by HIV infection. Thus, it seems that the VEGF autocrine loop functions differently in podocytes.…”
Section: Brief Communication Wwwjasnorgmentioning
confidence: 99%